Advanced Power Electronics for Grid-Integrated Renewable Energy Systems - Poonguzhali, S.; Mohapatra, Tapas Kumar; Boregowda, Vinay Kumar Sadolalu; Thakur, Ankita; Bhalla, Anubhav; Sairam, Kothakonda; Deepak, Shashikant (International Journal of Engineering, Science and Information Technology, 2025)
Incorporating Renewable Energy (RE) into the grid necessitates efficient and dependable power conversion phases, especially given the rising need for enhanced controllability and adaptability from the system. Powered by sophisticated control and data technologies, power electronics converters are crucial for large-scale RE production. The deployment of power converters has revealed several issues within traditional power grids, such as decreased system stability. The paper presents grid integration with power electronics for large-scale RE production. Technical challenges and specifications are examined, emphasising grid-dependent wind, solar power, and energy storage solutions. The fundamentals of energy production and converting control for individual electrical conversions (e.g., generalised current management) and at the system layer (e.g., coordinated functioning of large-scale energy networks) are briefly addressed. Further studies are proposed to enhance large-scale RE generating capabilities by integrating additional power electronics technologies.